Comparative Analysis of Aluminum and Iron Electrode Performance in Electrocoagulation for Industrial Wastewater Treatment - Hertiani, Hanna; Yuniarto, Adhi (Universitas Pendidikan Nasional, 2025)
This study presents a comparative analysis of electrocoagulation for industrial wastewater treatment, evaluating the performance of aluminum (Al) and iron (Fe) electrodes. The research combines a systematic literature review with experimental trials on a pilot-scale system. Experimental data for Al electrodes revealed inconsistent performance, showing a significant COD reduction at high pollutant concentrations but a paradoxical increase at low concentrations. This increase is attributed to the formation of soluble organic complexes. Conversely, experimental trials with Fe electrodes demonstrated consistent COD reduction across a range of influent concentrations. Fe electrodes successfully reduced COD by 1010 mg/L (from 2660 mg/L) and 790 mg/L (from 3220 mg/L) on two separate days, confirming their superior stability. These findings validate the theoretical advantages of Fe over Al electrodes and underscore the importance of selecting electrodes based on wastewater characteristics. The study concludes that Fe electrodes provide a more reliable and stable solution for treating fluctuating industrial wastewater.